Polyamine: A Potent Ameliorator for Plant Growth Response and Adaption to Abiotic Stresses Particularly the Ammonium Stress Antagonized by Urea - Sheng, Song; Wu, Changzheng; Xiang, Yucheng; Pu, Wenxuan; Duan, Shuhui; Huang, Pingjun; Cheng, Xiaoyuan; Gong, Yuanyong; Liang, Yilong; Liu, Laihua (Frontiers in Plant Science, 2022)
Polyamine(s) (PA, PAs), a sort of N-containing and polycationic compound synthesized in almost all organisms, has been recently paid considerable attention due to its multifarious actions in the potent modulation of plant growth, development, and response to abiotic/biotic stresses. PAs in cells/tissues occur mainly in free or (non- or) conjugated forms by binding to various molecules including DNA/RNA, proteins, and (membrane-)phospholipids, thus regulating diverse molecular and cellular processes as shown mostly in animals. Although many studies have reported that an increase in internal PA may be beneficial to plant growth under abiotic conditions, leading to a suggestion of improving plant stress adaption by the elevation of endogenous PA via supply or molecular engineering of its biosynthesis, such achievements focus mainly on PA homeostasis/metabolism rather than PA-mediated molecular/cellular signaling cascades. In this study, to advance our understanding of PA biological actions important for plant stress acclimation, we gathered some significant research data to succinctly describe and discuss, in general, PA synthesis/catabolism, as well as PA as an internal ameliorator to regulate stress adaptions. Particularly, for the recently uncovered phenomenon of urea-antagonized NH4+-stress, from a molecular and physiological perspective, we rationally proposed the possibility of the existence of PA-facilitated signal transduction pathways in plant tolerance to NH4+-stress. This may be a more interesting issue for in-depth understanding of PA-involved growth acclimation to miscellaneous stresses in future studies.